Influence of Physical Activity on Bone Strength in Children and Adolescents: A Systematic Review and Narrative Synthesis - PS Tan, Vina; M Macdonald, Heather; Kim, SoJung; Nettlefold, Lindsay; Gabel, Leigh; C Ashe, Maureen; A McKay, Heather (2014)
A preponderance of evidence from systematic reviews supports the effectiveness of weight‐bearing exercises on bone mass accrual, especially during the growing years. However, only one systematic review (limited to randomized controlled trials) examined the role of physical activity (PA) on bone strength. Thus, our systematic review extended the scope of the previous review by including all PA intervention and observational studies, including organized sports participation studies, with child or adolescent bone strength as the main outcome. We also sought to discern the skeletal elements (eg, mass, structure, density) that accompanied significant bone strength changes. Our electronic‐database, forward, and reference searches yielded 14 intervention and 23 observational studies that met our inclusion criteria. We used the Effective Public Health Practice Project (EPHPP) tool to assess the quality of studies. Due to heterogeneity across studies, we adopted a narrative synthesis for our analysis and found that bone strength adaptations to PA were related to maturity level, sex, and study quality. Three (of five) weight‐bearing PA intervention studies with a strong rating reported significantly greater gains in bone strength for the intervention group (3% to 4%) compared with only three significant (of nine) moderate intervention studies. Changes in bone structure (eg, bone cross‐sectional area, cortical thickness, alone or in combination) rather than bone mass most often accompanied significant bone strength outcomes. Prepuberty and peripuberty may be the most opportune time for boys and girls to enhance bone strength through PA, although this finding is tempered by the few available studies in more mature groups. Despite the central role that muscle plays in bones’ response to loading, few studies discerned the specific contribution of muscle function (or surrogates) to bone strength. Although not the focus of the current review, this seems an important consideration for future studies. © 2014 American Society for Bone and Mineral Research.